2013
DOI: 10.1016/j.livsci.2013.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea supplementation on nutrient digestibility, nitrogen utilisation and rumen fermentation in sheep fed diets containing dates

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authorsare permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 28 publications
(28 reference statements)
9
37
4
1
Order By: Relevance
“…Xin et al (2010) found similar results and suggested that higher acetate and lower butyrate concentrations in diets containing urea (FGU and SRU) resulted in lower conversion of acetate to butyrate in the rumen (Sharp et al, 1982;Sutton et al, 2003). Khattab et al (2013) observed higher acetate concentration when feeding urea, and an increase in microbial protein synthesis.…”
Section: Discussionmentioning
confidence: 74%
“…Xin et al (2010) found similar results and suggested that higher acetate and lower butyrate concentrations in diets containing urea (FGU and SRU) resulted in lower conversion of acetate to butyrate in the rumen (Sharp et al, 1982;Sutton et al, 2003). Khattab et al (2013) observed higher acetate concentration when feeding urea, and an increase in microbial protein synthesis.…”
Section: Discussionmentioning
confidence: 74%
“…However, there was no different effect among each level of U and M supplement. Rumen fermentation and digestibility were increased with the increasing levels of U supplement, which could be due to the increased rate of rumen microorganisms growth resulting from the presence of more available N in the form of ammonia from the hydrolysis of U (Boucher et al 2007;Khattab et al 2013;Kang et al 2015). In addition, Wanapat, Kang, Khejornsart et al (2013) reported that the supplementation of U and M could increase rumen degradability of whole-crop rice silage.…”
Section: Resultsmentioning
confidence: 98%
“…The true digestibility was increased regardless M dose (M0.5 = M1 = M2), and the NDF digestibility was the highest in M2 group. The lack of U influence on in vitro true and NDF digestibilities is rather surprising as it is supposed that rumen fermentation and digestibility increases with the U supplementation due to the increased rumen microorganisms growth rate as there is more available N in the form of ammonia from the urea hydrolysis (Khattab et al, 2013;Kang et al, 2015). Moreover, found that supplementation of U and M could increase rumen degradability of whole crop rice silage.…”
Section: Treatmentsmentioning
confidence: 99%